KANDUNGAN LOGAM TEMBAGA (Cu) PADA KARANG TIPE BRANCHING DI PERAIRAN KEPULAUAN KRAKATAU - Aditya Rahman (Bioscientiae, 2005)
Krakatau archipelago is one of the sea conservation which has a coral reef ecosystem dominated by those of branching type. On the other hand, Krakatau archipelago water is an international traffic line for ships along with hemmed in two regions, Bandar Lampung and Banten. Various human activities may lead to pollution, such as Cu which may enter the Krakatau archipelago waters and accumulate in their biota, including the sessile branching coral. The purpose of this research was to discover the concentration of Cu on branching coral reef in Sertung Island, Panjang Island, and Rakara Besar Island which are the part of Krakatau archipelago waters. The result indicated a level of pollution in Krakatau archipelago waters. The mean concentration of Cu in the three islands was 0.032 ppm. Presumably, the largest contributors of Cu pollutant in the Krakatau archipelago water are navigation activities through the strait and other human activities.